Assessment of double screening programmes via solid substrate fermentation (SSF) in a flask system and identification of lovastatin potential producer - Syarifah A. Rashid; Darah Ibrahim; I Nyoman Pugeg Aryantha (Syiah Kuala University, 2012)
Local economical substrates namely rice bran and unprocessed brown rice was applied into fermentation condition to produce a potent secondary metabolite compound, lovastatin. A basis condition of fermentation viz. 70% (v/w) of moisture content (adjusted to pH 6.0), 1x107 spore/ml of inoculum size, mixture of 1:1 substrates and 7 days of incubation period, was applied into SSF system. During a preliminary test, all of 72 fungi disclosed positive dark spot onto the thin layer chromatography plate (TLC). In order to verify the existence of lovastatin, the secondary screening which involving high performance liquid chromatography (HPLC) was conducted. Out of 72, only 71 fungi were detected as lovastatin producers and the highest production was stated from SAR I isolate with 68.72±0.84 mg lovastatin/g dry substrate and 0.87±0.03 mg glucosamine/g dry substrate of fungal growth. SAR I isolate was identified via colony and microscopic morphologies. Through the observations, SAR I isolate was identical to Aspergillus niger